Bidirectional Exchanges of Medical Students Between Institutional Partners in Global Health Clinical Education Programs: Putting Ethical Principles into Practice - Robert Rohrbaugh; Anne Kellett; Michael J. Peluso (Ubiquity Press, 2017)
Background One-third of US medical students participate in global health (GH) education, and approximately one-quarter of US medical schools have structured programs that offer special recognition in GH. GH clinical electives (GHCEs) are opportunities for students to experience a medical system and culture different from their own. GHCEs are administered through institutional affiliation agreements, often between an institution in a high-income country (HIC) and one in a low- or middle-income country (LMIC). Although these agreements suggest the exchange of students in both directions, GHCEs are traditionally characterized by students from HICs traveling to LMICs. Objectives The goal of this study was to investigate the availability of opportunities for students from LMICs participating in GHCEs at partner institutions in HICs and to describe the costs of these opportunities for students from LMICs. Methods We conducted a web-based search of 30 US institutions previously identified as having structured programs in GH. We determined which of these schools have programs that accept medical students from international schools for GHCEs, as well as the administrative requirements, types of fees, and other costs to the international student based on information available on the web. Descriptive statistics were employed for the quantitative analysis of costs. Findings We found that, although the majority of US institutions with structured GH programs sending students to sites abroad accept international students at their sites in the United States, nearly one-fifth of programs do not offer such opportunities for bidirectional exchange. We also characterized the substantial costs of such experiences, because this can represent a significant barrier for students from LMICs. Conclusions Access to GHCEs in US partner institutions should be an important underlying ethical principle in the establishment of institutional partnerships. The opportunities available to and experiences of students from LMIC partner institutions are important areas for future GH education research.